2010
DOI: 10.1590/s0100-83582010000200020
|View full text |Cite
|
Sign up to set email alerts
|

Suscetibilidade de genótipos de Lolium multiflorum ao herbicida glyphosate

Abstract: RESUMO -Objetivou-se com este trabalho avaliar o grau de tolerância dos genótipos diploides e tetraploides de L. multiflorum (azevém) ao herbicida glyphosate. Para isso, foram instalados quatro experimentos, sendo um para cada estádio fenológico do azevém (duas folhas, quatro perfilhos, pré-florescimento e formação de grãos). Utilizou-se delineamento em blocos casualizados com arranjo fatorial 2 x 6 (dois genótipos e seis doses do herbicida glyphosate: 240, 480, 960, 1.920, 3.840 e 7.680 g e.a. ha ) e uma test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(16 reference statements)
1
3
0
1
Order By: Relevance
“…ha -1 , rising to 87% at a 1440 g e.a. ha -1 dose and reaching 90% at a 2160 g e. a. ha -1 dose, characterizing control efficiency with the increase of this herbicide dose, which corroborates with DORS et al (2010) data, who working with different glyphosate rates, and tworyegrass genotypes (diploid and tetraploid), observed an increase in the control level by increasing glyphosate herbicide dose. These results show that although requiring high doses, the evaluated ryegrass biotype is sensitive to glyphosate.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…ha -1 , rising to 87% at a 1440 g e.a. ha -1 dose and reaching 90% at a 2160 g e. a. ha -1 dose, characterizing control efficiency with the increase of this herbicide dose, which corroborates with DORS et al (2010) data, who working with different glyphosate rates, and tworyegrass genotypes (diploid and tetraploid), observed an increase in the control level by increasing glyphosate herbicide dose. These results show that although requiring high doses, the evaluated ryegrass biotype is sensitive to glyphosate.…”
Section: Resultssupporting
confidence: 89%
“…In addition, weed species respond differently to herbicides when isolated or in combination (BARROSO et al, 2010) and in different weed plant stages. The more advanced the stage is, higher will be the herbicide dose required for an efficient control (DORS et al, 2010). Glyphosate is registered to control ryegrass at doses between 720 and 2160 g of acid equivalent (a.e.)…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also demonstrate a similar effect. Ryegrass plants sprayed with glyphosate showed that the control at the two-leaf stage was 67% higher when compared to plants treated at the tillering stage with the same herbicide dose (Dors et al, 2010). Plants of Eleusine indica at the two-leaf stage sprayed with glyphosate obtained a control 66% higher than that observed on plants treated at the tillering stage (Ulguim et al, 2013).…”
mentioning
confidence: 82%
“…Há relatos de que o azevém diploide apresenta suscetibilidade diferencial ao herbicida glyphosate, porém o tetraploide se mostra mais tolerante, fato que pode explicar o controle insatisfatório da planta daninha nas áreas de cultivo. Entretanto, o estádio fenológico de desenvolvimento das plantas pode afetar o grau de tolerância ao glyphosate em ambos os genótipos (Dors et al, 2010).…”
Section: Contagem Cromossômicaunclassified